Understanding circularity and transformative approaches and their role in achieving sustainability - Nhamo, L.; Mpandeli, S.; Liphadzi, S.; Mabhaudhi, Tafadzwanashe (CRC Press, 2024)
Circular and transformative approaches have emerged as alternatives to the current linear system, which has reached its limits, particularly when addressing today’s complex and interlinked challenges. Although linear models have been beneficial for decades, they have reached their threshold. The COVID-19 pandemic exposed the fragility of linear models in addressing interconnected challenges that cut across sectors. Focusing on one sector during a crisis only aggravates the stresses in other sectors. This is compounded by decision-makers who have often viewed the world linearly, thinking that clicking a button would get the economy and society back to normal. However, the reactive interventions that included the lockdowns implemented during the peak of the COVID-19 pandemic later resulted in job losses, company closures, debts, and economic recessions, demonstrating that linear models over-emphasise a limited set of system attributes, mainly efficiency, at the expense of other critical aspects. Compounded by climate change and other grand challenges, pandemics expose how unsustainable linear and sector-based approaches compromise resilience-building initiatives, allowing failure to cascade from one sector to another. Chapters in this book highlight how transformative and circular models contribute towards achieving cleaner production and sustainable development.